China's venture capital market : current legal problems and prospective reforms - Zhang, Lin (Elsevier Asian studies series., 2014)
The venture capital market in China has been developing for over twenty years. Over this period, the legal frameworks surrounding China's venture capital have evolved significantly. China's Venture Capital Market addresses this important topic and argues for further improvements in legal frameworks for venture capital in China. The book consists of five chapters, each covering an aspect of venture capital in China. The first chapter profiles the venture capital market. The second, third and fourth chapters consider the legal problems and suggest reform measures for fundraising in, operation o.